The Effects of Action Observation Speed on Motor Function in Patients with Chronic Low Back Pain: From Observation to Execution - Grande-Alonso, Mónica; Estradera-Bel, Manuel; Forner-Álvarez, Carlos; Cuenca-Martínez, Ferran; Vidal-Quevedo, Celia; Paris-Alemany, Alba; La Touche, Roy (Brain sciences, 2025)
Objective: The objective of this study was to examine the effect of observing actions at different speeds on the speed of motor task performance in subsequent actions. Methods: Sixty individuals, divided equally between those with non-specific chronic low back pain (NSCLBP) and asymptomatic subjects, were enrolled. Participants were further split into subgroups to observe lumbar flexion and Timed Up and Go (TUG) test actions at either a slow or fast pace, following a randomized assignment. For post-video observation, participants replicated the observed actions three times without specific performance instructions, allowing for the assessment of their execution speed. Results: The analysis revealed that individuals observing actions at a faster pace executed the subsequent motor tasks significantly quicker than their counterparts who viewed the same actions at a slower speed. This was consistent across both NSCLBP sufferers and asymptomatic subjects, indicating that the action observation (AO) speed directly influenced the execution speeds of lumbar flexion and TUG test movements. Conclusions: The findings demonstrate that AO speed significantly affects the pace of motor execution, irrespective of NSCLBP presence. This underscores the potential of utilizing varied AO speeds as a strategic component in clinical practice, particularly for enhancing motor planning and execution in physical therapy settings. The study highlights the importance of incorporating AO speed variations into therapeutic interventions for improving patient outcomes in motor task performance.